Through collaboration to sharawadji: immediacy, mediation and the voice. Issue 3 (1st October 2016) - Westerside, Andrew; Blain, Martin; Turner, Jane
ABSTRACT: This article analyses the composition and experience of Proto-type's The Good, the God and the Guillotine (2014) from three critical positions central to the making process: Andrew Westerside, from the position of director and performer-singer; Martin Blain, from the position of composer-performer; and Jane Turner, from the position of dramaturge and spectator-listener. It addresses an emergent connection between the sharawadji effect and the techno-sublime, made possible in this performance through the disturbances of technology and the 'technologically uncanny'. The objective of the article is twofold. Firstly, it demonstrates how both internally (to the performer) and externally (to the spectator) experiences of sharawadji and the sublime might emerge. Secondly, it proposes these experiences – notably sharawadji – as a product of the interdisciplinary process, and suggests in doing so a productive relationship between the often conflicting or unresolved dramaturgies that are created across performance disciplines.